A survey of asthma mortality in patients between ages 35 and 64 in the Greater London hospitals in 1971. Issue 3 (June 1975) - Cochrane, G M; Clark, J H
Abstract : We have examined the death certificates from all patients aged 35-64 years who were recorded as dying from asthma in Greater London Council hospitals in 1971. Of the 47 death certificates studied, nine suggested that the primary cause of death was not asthma. From the remaining 38 deaths we have obtained 36 case records and found that 15 deaths occurred outside hospital and another two patients died in hospital having been admitted in a stable state. We have examined the remaining 19 case records to find out the circumstances of death in patients with asthma who die in hospital. We have been unable to exclude the possibility that many of the deaths in hospital were avoidable. Assessment of severity in most patients was incomplete, as judged by a retrospective analysis of case records, and many of the patients would be regarded as having had insufficient treatment. Four patients did not receive corticosteroids and in a further three the dose given was small. No physiological assessment of airflow obstruction was made in over half the patients. A comparison with 19 survivors of an admission to hospital with asthma did not provide enough information to account for the deaths. The survivors were in hospital for a shorter period of time, were slightly less ill, and were given comparable treatment regimens. Both groups of patients were inadequately assessed, and sedatives were given to approximately 70% of all subjects studied. The deaths in hospital usually occurred suddenly in the early morning in general medical wards.